Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Pada Dinas Pendapatan Daerah Kota Kendari - Susilawati, Andi (JURNAL AKUNTANSI, 2016)
Â  Regional Revenue Office Kendari budgeting system using bottom up with involving all employees in the Regional Revenue Office of Kendari. By involving all employees is expected to improve managerial performance. This study aims to determine whether the involvement of all employees in the Department of Revenue can improve managerial performance. Data retrieval technique using questionnaires with sampling methods using purposive sampling method with the results of a sample of 24 people. The analysis model used in this study is a model of simple linear regression analysis was performed with a computer program SPSS version 16.0 for Windows The results showed that the significant test of individual parameters (t test) showed that the variables significantly affect budgetary participation on managerial performance with tcount of 10,345 and a significance value of 0.000. Keywords: budget participation, managerial performance